From Conventional to Advanced Therapies: A National Health Registry Report (2016-2022) on DMARDs in Rheumatoid Arthritis Treatment in Turkey - Ata N; Satış H; Küçükşahin O; Karabulut E; Ayan G; Erden A; Bilgin E; Armağan B; Tecer D; Babaoğlu H; Sarı A; Kılıç L; et al. (Biologics: Targets & Therapy)
Naim Ata,1 Hasan Satış,2 Orhan Küçükşahin,3 Erdem Karabulut,4 Gizem Ayan,5 Abdulsamet Erden,6 Emre Bilgin,7 Berkan Armağan,8 Duygu Tecer,9 Hakan Babaoğlu,8 Alper Sarı,10 Levent Kılıç,5 Mustafa Mahir Ülgü,11 Mustafa Okan Ayvalı,11 Şuayip Birinci,12 Umut Kalyoncu5 1Department of Strategy Development, Republic of Turkey, Ministry of Health, Ankara, Turkey; 2Department of Rheumatology, University of Health Sciences Abdurrahman Yurtaslan Oncology Hospital, Ankara, Turkey; 3Department of Rheumatology, Ankara Yıldırım Beyazit University, Ankara City Hospital, Ankara, Turkey; 4Department of Biostatistics, Hacettepe University Faculty of Medicine Department, Ankara, Turkey; 5Department of Internal Medicine, Division of Rheumatology, Hacettepe University Faculty of Medicine, Ankara, Turkey; 6Department of Internal Medicine, Division of Rheumatology, Gazi University Medical Faculty, Ankara, Turkey; 7Department of Internal Medicine, Division of Rheumatology, Sakarya University Medical Faculty, Sakarya, Turkey; 8Department of Internal Medicine, Division of Rheumatology, University of Health Sciences Ankara City Hospital, Ankara, Turkey; 9Department of Internal Medicine, Division of Rheumatology, University of Health Sciences Gulhane Research and Training Hospital, Ankara, Turkey; 10Department of Internal Medicine Division of Rheumatology, University of Health Sciences Etlik City Hospital, Ankara, Turkey; 11General Directorate of Health Information Systems, Republic of Turkey, Ministry of Health, Ankara, Turkey; 12Republic of Turkey, Ministry of Health, Ankara, TurkeyCorrespondence: Hasan Satış, Department of Rheumatology, University of Health Sciences Abdurrahman Yurtaslan Oncology Hospital, Ankara, Turkey, Email hasansats@gmail.comObjective: There are national and international guidelines on the optimal use of disease-modifying anti-rheumatic drugs. In this study, we aimed to provide critical insights into the real-world efficacy and adherence of these DMARDs, providing a data-driven basis for optimizing treatment paradigms for RA within the national healthcare framework.Methods: This nationwide cohort study utilized data from the Turkish Ministry of Health National Electronic Database, known as E-Pulse between January 2016 and December 2022. In this analysis, cases of RA were identified using ICD-10 codes two times at least 30 days apart Treatment prescriptions were recorded based on their prescription at baseline and follow-up.Results: There were a total of 347,902 RA (79.5% female) patients in the E-Pulse system. The mean (SD) age of RA patients was 59.1 (14.8) years Methotrexate and sulfasalazine (35.1% vs 30.5%, OR 95% CI 0.81 usage was more common in men and hydroxychloroquine was more common in women 46.764 (13.4%) patients were prescribed bDMARD and/or tsDMARD 494.499 times. AntiTNF drugs are the most commonly prescribed drugs. This is followed by B-cell blockers, JAK inhibitors, anti-IL6 and T-cell blockers.Conclusion: Turkish national health database highlights the widespread use of synthetic DMARDs in treating rheumatoid arthritis (RA). While traditional DMARDs like methotrexate and hydroxychloroquine are favored the cautious use of advanced therapies, particularly anti-TNFs, suggests a potential for optimizing treatment protocols.Keywords: rheumatoid arthritis, treatment, nation-wide, disease modifying drug